Legal Protection For Workers/Medical Workers against Case of Diseases Due to Covid-19 - Gresa Sekardatun; Siti Rodhiyah Dwi Istinah (Jurnal Daulat Hukum, 2021)
The purpose of this research is to provide legal protection To find out and analyze all Medical Workers/Laborers affected by occupational diseases due to Corona Virus Disease 2019 (Covid-19) in Semarang City, they have obtained their rights in accordance with existing laws and regulations. The research method used is the sociological juridical approach method, descriptive analysis research specifications, the research data source uses primary data and secondary data, which includes primary legal materials, secondary legal materials and tertiary legal materials. Data analysis using qualitative analysis methods. The result is the government, through the Labor Inspectorate, needs to provide guidance and outreach to companies so that employers will understand and understand the benefits of Work Accident Security (JKK), which is very much needed during a pandemic like this, because medical workers/laborers are at the forefront of carrying out their duties to treat patients who have being exposed to COVID-19 must be protected by registering all medical workers/laborers in the BPJS Of Workers Work Accident Insurance (JKK).